Giroux, H. (2023) On Critical Pedagogy. (2ª Ed.). Bloomsbury. p. 265. (Revista Lusófona de Educação, 2025)
Henry Giroux is a Professor of Cultural Studies, holding the Chair for Scholarship in the Public Interest in the Department of English and Cultural Studies, as well as the Paulo Freire Chair. Like Paulo Freire, he is recognized as one of the founders of critical pedagogy. He has published around 67 books, including his most recent works: The Terror of the Unforeseen (2019) and Race, Politics, and Pandemic Pedagogy: Education in a Time of Crisis (2021).The publication under analysis is the second edition (2023) of On Critical Pedagogy, first published in 2011, and updated to reflect the contemporary sociopolitical context. The book is divided into 11 chapters, three of which are dedicated to examining the rise of neofascist culture and the post-truth era that has characterized the world since Donald Trump's presidency.It is written in a critical tone, addressing the role of culture and critical pedagogy in constructing freedom, democracy, and individual subjectivity.The book highlights the role of schools and teachers as transformative agents who enact critical pedagogy and reflects on the negative impact of neoliberal policies on curriculum reform. Beyond critique, Giroux offers alternatives for educational institutions to reclaim their role in defending freedom and social justice.